KONSEPTUALISASI TENTANG PENGUATAN MANAJERIAL KELOMPOK TERNAK PEMBUDIDAYA HEWAN RUMINANSIA BERJENIS KAMBING - Aji Fanny Permana (J-EBI: Jurnal Ekonomi Bisnis Islam, 2023)
Abstract The success of agricultural development, especially in the field of animal husbandry through the cultivation of ruminant livestock of the goat type, is largely determined by the ability or capacity of its human resources. As agents of development, breeders should ideally have adequate knowledge and skills in managing livestock business. In fact, the condition of Human Resources (HR) in Indonesia currently does not meet the expected qualifications to form advanced livestock. Therefore, improving the quality of HR in all aspects is absolutely necessary. Improving the quality of HR includes aspects of mastery of knowledge, livestock skills, business management, and capital strengthening. It is no less important is the development of entrepreneurial character. To overcome these problems, current government policies are mostly directed at empowering livestock groups towards strong, sustainable, independent and solid livestock groups, not just groups that are just a formality. This is because livestock groups are formed by and for breeders, so it is hoped that through these livestock groups, breeders can access all resources, such as HR, Natural Resources (NR), capital, information, as well as facilities and infrastructure in developing a successful livestock business. worked on. Therefore, in addition to the need to explore the potential and comprehensive knowledge about the management of non-HR in the livestock business, managerial strengthening of livestock groups, especially for goat cultivating livestock groups, is also an instrument that is no less important. In fact, this is vital to be understood and applied optimally by livestock groups and socialized thoroughly to administrators and members, so that the livestock business that is managed becomes controlled and effective to be directed at the desired target or achievement.Keywords: Conceptualization, Managerial Strengthening, Cultivation, Ruminant Livestock.